A measure for identifying substantial geographic concentrations*. (29th July 2016) - van Egeraat, Chris; Morgenroth, Edgar; Kroes, Rutger; Curran, Declan; Gleeson, Justin
Abstract: Regional industrial policy emphasizes the notion of building on existing concentrations of competitive firms. A range of measures to identify such concentrations has been put forward in the literature. These measures, however, do not identify substantial concentrations which have the best potential for further development, tend to concentrate on scale measured by employment, and are applied using data for pre‐specified administrative boundaries. This paper presents a new concentration index that identifies substantial concentrations and utilizes information on both the number and size of plants. It also proposes a method for generating relevant industry‐specific spatial units.